Genomic analysis of filoviruses associated with four viral hemorrhagic fever outbreaks in Uganda and the Democratic Republic of the Congo in 2012 - Albariño, C.G. (Virology, 2013)
In 2012, an unprecedented number of four distinct, partially overlapping filovirus-associated viral hemorrhagic fever outbreaks were detected in equatorial Africa. Analysis of complete virus genome sequences confirmed the reemergence of Sudan virus and Marburg virus in Uganda, and the first emergence of Bundibugyo virus in the Democratic Republic of the Congo.